Ingvar the Far-Travelled: between the Byzantium and Caucasus. A Maritime Approach to Discussion - Böhm, Marcin (Studia Ceranea, 2019)
The Journey to the East of the Viking Ingvar the Far-Traveled is one of the events that fit into the history of medieval relations of the Scandinavians with the world of Byzantium. It was a fateful expedition taking place between 1036 and 1041, and to this day it is a source of many controversies and speculations of researchers. The findings of the present paper suggest that the journey did not necessarily proceed to the lands of the Saracens or Byzantium but may have been part of the game played by Constantinople with its ally Tmutarkan, which opposed Jaroslav the Wise, these events unfolding in the north-eastern waters of the Black Sea.